The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s0100-29452013000400008
|View full text |Cite
|
Sign up to set email alerts
|

Estádio de maturação para o período ideal de colheita de maçãs 'Daiane' destinadas à armazenagem

Abstract: Este trabalho foi realizado com o objetivo de identificar índices de maturação para o ponto ideal de colheita, de maçãs 'Daiane', destinadas a longos períodos de armazenamento. Maçãs foram colhidas semanalmente, em dois pomares comerciais, no período de 113 a 149 dias após a plena floração (DAPF), e armazenadas por 180 ou 240 dias a 0,7ºC, em atmosfera controlada. Medidas do estádio de maturação e da qualidade das maçãs foram realizadas um dia após a colheita e após a armazenagem. Atributos da aparência (cor v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 13 publications
0
6
1
8
Order By: Relevance
“…Studies have shown that apples continue to grow during the ripening on the tree (STANGER et al, 2013). However, the present work shows that there is no trend of continuous increase in size (reduction of class size) throughout the harvest period of apple industry.…”
Section: Resultscontrasting
confidence: 56%
See 4 more Smart Citations
“…Studies have shown that apples continue to grow during the ripening on the tree (STANGER et al, 2013). However, the present work shows that there is no trend of continuous increase in size (reduction of class size) throughout the harvest period of apple industry.…”
Section: Resultscontrasting
confidence: 56%
“…The quality of apples (Malus domestica Borkhausen) can be negatively affected, both by excessive early and late harvest, especially when fruits are intended for long-term storage. In addition, the harvesting time also influences important characteristics that define the commercial value of fruits such as size and peel color (PLOTTO et al, 1995, STANGER et al, 2013, SCOLARO et al, 2015.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations